A Multi-sensor View of the 2012 Central Plains Drought from Space - Wang, Jun; Kessner, Amy L.; Aegerter, Clint; Sharma, Ambrish; Judd, Laura; Wardlow, Brian; You, Jinsheng; Shulski, Martha; Irmak, Suat; Kilic, Ayse; Zeng, Jing (Frontiers in Environmental Science, 2016)
In summer of 2012, the Central Plains of the United States experienced its most severe drought since the ground-based data record began in late 1900s. By using comprehensive satellite data from MODIS and TRMM, along with in-situ observations, this study documents the geophysical parameters associated with this drought, and thereby providing, for the first time, a large-scale observation-based view of the extent to which the land surface temperature and vegetation can likely be affected by both the severe drought and the agriculture’s response (irrigation) to the drought. Over non-irrigated area, 2012 summer daytime land surface temperature (LST) and Normalized Difference Vegetation Index (NDVI) monthly anomalies (with respect to climate in 2002-2011) are often respectively greater than 5 K and negative, with some extreme values of 10 K and -0.2 (i.e., no green vegetation). In contrast, much smaller anomalies (< 2 K) of LST and nearly the same NDVI are found over irrigated areas. Precipitation received an average of 5.2 cm less, while both fire counts and fire radiative power were doubled, thus contributing in part to a nearly 100% increase of aerosol optical depth in many forested areas (close to intermountain west). Water vapor amount, while decreased over the southern part, indeed slightly increased in the northern part of Central Plains. As expected, cloud fraction anomaly is negative in the entire Central Plains; however, the greatest reduction of cloud fraction is found over the irrigated areas, which is in contrast to past modeling studies showing more irrigation, because of its impact on LST, may lead to increase of cloud fraction.